Effect of freezing–thawing cycles and high temperatures on concretes containing partial replacement of fine grain blast and Electric Arc Furnace slags - Seyed Hosein Ghasemzadeh Mousavinejad; Sepehr Ghorbani GilKalaye (Discover Materials)
Abstract This study examines the effects of local industrial by-products, such as iron slag and steel slag, as partial replacements of fine grain at 10%, 15%, and 25%, individually and combined. The research evaluates the impact on mechanical resistance under freeze–thaw cycles and high temperatures. Additionally, the study explores the effects of incorporating 0.3% polypropylene fibers by volume and 10% microsilica by cement weight (500 kg/m3). The durability of concrete samples exposed to freezing–thawing at the age of 28 days with 100 cycles and at temperatures of 400 °C and 800 °C at the age of 90 days in the gas furnace were investigated in terms of compressive strength. Samples subjected to 100 freeze–thaw cycles showed increased porosity and expansion of microcracks, leading to a loosened macrostructure and a 0.8% decrease in weight. Findings indicate that the partial replacement of slag in the fine grain and combining these materials with polypropylene and microsilica fibers improved mechanical properties like compressive strength. Additionally, the freeze–thaw cycle caused a 32.46% decrease in sample resistance compared to the control state. Moreover, incorporating 10% slag enhanced the mechanical properties of samples at 400 °C and 800 °C, with a lower resistance loss when compared to designs without additives. The inclusion of 10% microsilica and 0.3% polypropylene fibers, however, reduced sample resistance at 800 °C compared to 400 °C. Microstructural analysis of GGBS in concrete using Scanning Electron Microscopy (SEM) revealed that the addition of GGBS produces a denser matrix populated with more angular particles, resulting in improved bonding properties compared to plain concrete.